ASiDCON2018: Proceeding Book - Ibrahim, Salizatul Ilyana (Center of Foundation Studies, 2018)
Proceeding book for ASiDCON2018 with the theme, “Navigating the Future through Multidisciplinary Research”. ASiDCON2018 will provide a platform for academics, researchers and professionals from various backgrounds and disciplines to share the latest findings (or expected results of research work and research progress) in their related fields.